Examining Continuance Intention to Use the Jamsostek Mobile (JMO) Application: A UTAUT Approach with Experience as a Moderating Variable - Wahyu Dwi Atmoko (BPJS Ketenagakerjaan, 2026)
The declining percentage of Jamsostek Mobile (JMO) application users despite a significant increase in active BPJS Ketenagakerjaan participants poses a challenge to maintaining the sustainable use of the application. This study examines the factors influencing the continuance intention to use the JMO application of BPJS Ketenagakerjaan using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, with user experience as a moderating variable. Data were collected from 100 active BPJS Ketenagakerjaan participants registered as JMO users in the Central Java and Yogyakarta regions in 2023 and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that performance expectancy and facilitating conditions are significant predictors of continuance intention, while effort expectancy and social influence are not. Furthermore, experience does not significantly moderate any of the proposed relationships, suggesting that its moderating role may be context-dependent and less relevant among users with already high levels of digital familiarity. These findings provide important insights for public digital service providers in formulating strategies to strengthen sustained application use through functional perceptions and supporting conditions.